Characterization of the invitro cytotoxic effects of brachydins isolated from Fridericia platyphylla in a prostate cancer cell line. Issue 15 (17th August 2020) - Nunes, Higor Lopes; Tuttis, Katiuska; Serpeloni, Juliana Mara; Nascimento, Jessyane Rodrigues do; da Rocha, Claudia Quintino; Silva, Viviane Aline Oliveira; Lengert, André van Helvoort; Reis, Rui Manuel; de Syllos Cólus, Ilce Mara
ABSTRACT: Brachydins (Br) A, B, and C are flavonoids extracted from Fridericia platyphylla (Cham.) L.G. Lohmann roots (synonym Arrabidaea brachypoda ), whose extract previously exhibited cytotoxic and antitumor activity. In vitro cell culture of human prostate tumor cell line (PC-3) was used to determine cell viability as evidenced by MTT, neutral red, and LDH release using nine concentrations (0.24 to 30.72 µM) of each brachydin. A triple-fluorescent staining assay assessed the mechanism resulting in cell death. Genomic instability and protein expression were evaluated using comet assay and western blot analysis, respectively. The pro-oxidant status was analyzed using the5-(and-6)-chloromethyl-2′, 7′-dichlorodihydrofluorescein diacetate (CM-H2 DCFDA) probe. The IC50 values for brachydins BrA, BrB, and BrC were 23.41, 4.28, and 4.44 µM, respectively, and all compounds induced apoptosis and necrosis. BrB and BrC increased p21 levels indicating a possible G1 cell cycle arrest. BrA (6 µM) and BrB (3.84 µM) decreased phospho-AKT (AKT serine/threonine kinase) expression, which also influenced cell cycle and proliferation. BrA, BrB, and BrC elevated cleaved PARP (poly (ADP-ribose) polymerase), a protein related to DNA repair and induction of apoptotic processes. Therefore, this study determined the IC50 values of brachydins in the PC-3 cell line as well as the influence on cell proliferation and cell death processes, such as apoptosis and necrosis, indicating the proteins involved in these processes. Abbreviations: ANOVA: Analysis of Variance; BrA: Brachydin A; BrB: Brachydin B; BrC: Brachydin C; CGEN: Genetic Heritage Management Council; CID: Compound identification number; CM-H2 DCFDA, 5-(and-6)-chloromethyl-2′, 7′-dichlorodihydrofluorescein diacetate, acetyl ester; CO2 : Carbon dioxide; DMSO: Dimethyl sulfoxide; DNA: Deoxyribonucleic acid; DTT: Dithiothreitol; DXR: Doxorubicin; ECL: Chemiluminescence; EDTA: Ethylenediaminetetraacetic acid; FBS: Fetal bovine serum; H2 O2 : Hydrogen peroxide; HRMS: High-Resolution Mass Spectrometry; IC50: Half maximal inhibitory concentration; LDH: Lactate dehydrogenase; MTT, 3-[4, 5-Dimethylthiazol-2-yl]-2, 5-diphenyl tetrazolium bromide; Na3VO4: Sodium Orthovanadate; NaOH: Sodium hydroxide; NCBI: National Center for Biotechnology Information; NMR: Nuclear Magnetic Resonance; PBS: Phosphate buffer saline; PCR: Polymerase chain reaction; PSMF: Phenylmethylsulfonyl fluoride; RPMI: Roswell Park Memorial Institute Medium; SDS-PAGE: Sodium Dodecyl Sulfate-Polyacrylamide gel electrophoresis; STR: Short tandem repeat; TBS-T: Tris-buffered saline and Polysorbate 20; UPHLC: Ultra-Performance Liquid Chromatography